1990
DOI: 10.1159/000177588
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Obesity, Leanness and Anorexia nervosa in Japanese Boys and Girls Aged 12–14 Years

Abstract: Body weight and height of Japanese boys and girls aged 12–14 years were measured to calculate the prevalence of obesity, leanness and anorexia nervosa. In boys, the prevalence of obesity as well as leanness was significantly higher in the areas where population density was lower and among the boys who attended schools with smaller numbers of pupils. In the girls, these findings were similar to the boys. On the other hand, anorexia nervosa was found in girls only more commonly in the areas with higher populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
1

Year Published

1992
1992
2010
2010

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 9 publications
0
17
0
1
Order By: Relevance
“…Measurement of body weight can clarify, though not completely, variations in fat tissues. On clinical basis, indices of weight (Rolland-Cachera et al, 1982;Malina et al, 1986;Ohzeki et al, 1990) such as body mass index (BMI) and %Wt have been most commonly used to screen undernourished or obese children and adolescents because obesity is defined as accumulation of excess adipocytes, which synthesize and secrete leptin into the circulation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Measurement of body weight can clarify, though not completely, variations in fat tissues. On clinical basis, indices of weight (Rolland-Cachera et al, 1982;Malina et al, 1986;Ohzeki et al, 1990) such as body mass index (BMI) and %Wt have been most commonly used to screen undernourished or obese children and adolescents because obesity is defined as accumulation of excess adipocytes, which synthesize and secrete leptin into the circulation.…”
Section: Discussionmentioning
confidence: 99%
“…During infancy through adolescence, previous reports documented age-and sex-related changes as well as nutrition-induced variations in fat mass in Western countries (Tanner & Whitehouse, 1975;Malina et al, 1986;Gasser et al, 1994) and also in Asia including Japan (Ohzeki et al, 1990(Ohzeki et al, ,1996. After a decrease in percentage of body fat with age during early childhood, adolescent girls gain more adipose tissue than boys to exhibit secondary sexual characteristics (Tanner & Whitehouse, 1975;Ohzeki et al, 1996).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Um deles encontrou que a prevalência de AN em escolas de 2 o grau na cidade de Kyoto era de 0,2%, mas nas áreas rurais ao redor, a prevalência foi 4 vezes menor (0,05%) 18 . Outro estudo reportou a taxa de prevalência de AN em meninas japonesas três vezes mais baixa nas áreas rurais, do que urbanas 19 . Obtendo resultados diferentes, alunas de escolas públicas da zona rural no sul da Itália foram avaliadas e encontrou-se prevalência semelhante a de áreas urbanas ou metropolitanas 20 .…”
Section: Fatores De Riscounclassified
“…In this study, normal ranges of SFT in Japanese children are demonstrated and their racial characteristics are compared to Caucasians. It is sug gested that children with EW of 10-30% are heterogenous and determination of fat volume is essential to confirm the diagno sis of obesity in these subjects.In recent years, obesity has been the most frequent nutritional problem in childhood [1][2][3][4][5] in developed countries instead of malnutri tion, which is of course still important in some parts of the world. Although morbid obesity is easy to diagnose by seeing patients' body habitus [ 1 ].…”
mentioning
confidence: 99%